Atrasos aéreos: uma nova medida baseada na análise envoltória de dados - Barros, Tatiana Dodsworth de (2008)
Flights delays had always been one of the main problems in the air transportation. Due to the recent chaos in the Brazilian airports the media began to notice the situation of the flights delays. The form to measure these delays became a question of great importance. Such a measure already existed, but it lost credibility when the Brazilian Agency for Air Transportation changed the calculus methodology for domestic flights. Even before this change, the punctuality index presented severe drawbacks. The main goal of this thesis is to present a new index. Our index will take into account both the departure and the arrivals delays. We do not want to say that a flight is, or is not, delayed. We intend to quantify the delays. To do so, we will propose an index based on Data Envelopment Analysis (DEA)